Effectiveness of mirror therapy through functional activities and motor standards in the motor recovery in post stroke hemiplegic patients: a prospective randomized controlled trial in a tertiary care hospital in Northeast India - Yumnam, Ningthemba; Akoijam, Joy Singh; Oinam, Joymati (International Journal of Research in Medical Sciences, 2019)
Background: Upper limbs are very important to motor functionality. However, in majority of stroke patients, arm functions are impaired resulting in disabilities and restrictions to function. Therefore, the objective of this study was to assess the effectiveness of mirror therapy in the motor recovery of upper extremity in the post stroke hemiplegic patient. Methods: A prospective randomized controlled trial was conducted among 72 post stroke patients aged 35-65 years having hemiparesis attending the PMR OPD in RIMS, Manipur from 2013 to 2016. Assessment was done for FIM self care and Brunnstrom stages of motor recovery at baseline and 1 month and 6 month of post treatment. Both the study and control group participated in a stroke rehabilitation programme and study group was given mirror therapy in addition. Descriptive statistics such as mean, standard deviation and inferential statistics like Chi-square test, Student’s t test, and ANOVA were used. A p-value <0.05 was taken as statistically significant. Results: Mean age were 54.56±7.61 years (study) and 55.11±7.99 years (control). Majority of them were males (61.1%). Significant improvement was noted in the study group from baseline to 1 month and 6 months follow up. Mean score comparison of FIM self care between study and control group from baseline to 1 month was (28.28±3.11 to 34.11±2.59 vs 28.00±4.30 to 29.50±4.58) and from 1 to 6 months follow up was (34.11±2.59 to 37.83±2.04 vs 29.50±4.58 to 32.44±4.82) respectively. Conclusions: There was a significant improvement in hand function regarding both motor recovery and daily self care activities in the study group.